The Chronic and Unpredictable Stress Suppressed Kisspeptin Expression during Ovarian Cycle in Mice - Seung-Joon Kim (The Korean Society of Animal Reproduction and Biotechnology, 2019)
Chronic and unpredictable stress can disrupt the female reproductive system by suppression for secretion of gonadotrophin-releasing hormone (GnRH) and gonadotrophin, resulted in ovarian malfunction and infertility. In the recent days, kisspeptin has been highly highlighted as a hypothalamic peptide which directly stimulates synthesis and release for GnRH. However, in spite of the key role of kisspeptin in the female reproductive system, little information is still available on the changes of its expression during ovarian cycle under stressed condition. Therefore, we induced chronic and unpredictable stress series to the female mice to analyze kisspeptin expression in the brain and ovary. Stressed mice exhibited changes of behavior and body weight gain during the stress assessment, which suggested that the present stress model in mice was successfully established. In the brain level, kisspeptin expression was attenuated than control. In the ovary level, the stressed mice displayed irregularly shrunk oocytes with broken zona pellucida throughout the follicle stages, pyknotic granulosa cells, decreased number of developing follicles and increased number of atretic follicles than the control. In case of kisspeptin expression in the whole ovary tissue, the expression level was decreased in the stressed mice. In detail, the less intensity of kisspeptin expression in the antral follicles phase was observed in the stressed mice than control mice, indicating that local function of kisspeptin during ovary cycle is highly associated with development of ovarian follicles. We expect that the present study has important implications for the fields of reproductive biology.